Chemical constituents from the fruits of Rhus typhina L. and their chemotaxonomic significance. (December 2016) - Qiu, Da-Ren; Wang, Da-Cheng; Yang, Sheng-Xiang; Zhang, Ya-Mei; Wei, Dong-Sheng; Zhang, Ming-Zhe; Sun, Jin-Zhu; Cong, Jie; Guo, Jie; He, Shu-Liang; Qin, Jian-Chun
Abstract: This work describes the isolation and characterization of twenty-nine compounds from the fruits of Rhus typhina L., including eleven flavonoids (1–11 ), eleven phenols (12–22 ), two pentacyclic triterpenes (23–24 ), two organic acids (25–26 ), one lumichrome (27 ), one courmarin (28 ) and one pyrimidine (29 ) on the basis of their spectroscopic data. Compounds apigenin (1 ), daidzein (4 ), orobol (5 ), 3′, 5, 5′, 7-tetrahydroxyflavanone (6 ), naringenin (7 ), butein (8 ), (-)-catechin (9 ), quercetin-3- O - α - L -(3″- O -galloyl)-rhamnoside (11 ), 2-hydroxybenzoic acid (13 ), 4-hydroxybenzaldehyde (14 ), vanillin (15 ), methyl 3, 4-dihydroxybenzoate (16 ), 3, 5-dihydroxybenzamide (18 ), tyrosol (19 ), caffeic acid (20 ), 3-(2, 4, 6-trihydroxyphenyl)-1-(4-hydroxyphenyl)-propan-1-one (21 ), phlorizin (22 ), friedelin (23 ), oleanolic acid (24 ), 4, 4-dimethyl-heptanedioic acid (25 ), anthranilic acid (26 ), lumichrome (27 ), scoparone (28 ) and uracil (29 ) have not been recorded before in this plant. This is the first report on the occurrence of compounds4–7, 9, 11, 13–14, 16, 18–21, 25–29 from the genus Rhus . Moreover, the chemotaxonomic significance of these isolated compounds was also summarized. Highlights: Twenty-nine compounds were isolated from the fruits of Rhus typhina L.. Eighteen compounds were obtained from the genus Rhus for the first time. The chemotaxonomic significance of these isolated compounds was summarized.